Multi-region optimal deployment of renewable energy considering different interregional transmission scenarios. (1st August 2016) - Wang, Ge; Zhang, Qi; Mclellan, Benjamin C.; Li, Hailong
Abstract: Renewable energy is expected to play much more important role in future low-carbon energy system, however, renewable energy has problems with regard to load-following and regional imbalance. This study aims to plan the deployment of intermittent renewable energy in multiple regions considering the impacts of regional natural conditions and generation capacity mix as well as interregional transmission capacity using a multi-region dynamic optimization model. The model was developed to find optimized development paths toward future smart electricity systems with high level penetration of intermittent renewable energy considering regional differences and interregional transmission at national scale. As a case study, the model was applied to plan power generation in nine interconnected regions in Japan out to 2030. Four scenarios were proposed with different supporting policies for the interregional power transmission infrastructures and different nuclear power phase-out scenarios. The analysis results show that (i) the government's support for power transmission infrastructures is vital important to develop more intermittent renewable energy in appropriate regions and utilize renewable energy more efficiently; (ii) nuclear and renewable can complement rather than replace each other if enough interregional transmission capacity is provided. Highlights: Plan the optimal deployment of intermittent renewable energy in multiple regions. A multi-region dynamic optimization model was developed. The impacts of natural conditions and interregional transmission are studied. The government's support for transmission is vital important for renewable energy. Nuclear and renewable can complement rather than replace each other.